Nurse Caring Behavior Experienced Patients Based on Swanson's Theory in The Inpatient Room of X Hospital Batam - Putra Hidayat, Muhammad; Muharni, Sri; Christya Wardhani, Utari (Indonesian Health Journal, 2023)
Caring is an act related to respect, understanding, and responsibility. In nursing services, there are still attitudes of nurses who still need to implement caring behaviour optimally. In Indonesia, the majority of low caring behaviour is performed by nurses, as much as 56.3%. A preliminary study was conducted at a private hospital in Batam City; it was found that patients said nurses had only interacted with patients for a short time. This study aimed to explore patient experiences related to caring behaviour based on Swanson's theory in the Inpatient Room of X Hospital Batam. This research method uses qualitative methods with a phenomenological approach. Data was collected using semi-structured in-depth interviews, recorded using mobile phones for 7 participants according to the inclusion and exclusion criteria, and the data analysis process used Creswell data analysis. The results of the study obtained three themes, namely, (1) growing confidence and trust in patients, (2) showing professionalism to patients, and (3) providing information and providing support to patients. This study concluded that the nurses had caring behaviour according to Swanson's theory, but from the participants' experiences, not all aspects of Swanson's caring process were reflected in this study. It is hoped that future researchers can explore all aspects of Swanson's caring theory or prove it was using other theories related to caring behaviour given by nurses.